Nominal KAŊ form in Basse Mandinka: Its cognitive mapping and taxonomical status (Part 2) - Andrason, Alexander (Lingua Posnaniensis, 2014)
Purpose: The present study, divided into a series of two papers, provides a detailed empirical descrip- tion and cognitive-grammaticalization analysis of the meaning of a Mandinka verbal expression com- pounded of the non-verbal predicator be ‘be’, a verbal noun expressing a given action and the postposi- tion kaŋ ‘on, at’ (so-called the nominal kaŊ form). Method: The author follows the cognitive approach to verbal semantics which consists first of determin- ing the exact range of contextually induced senses and next of unifying such values into a consistent map based upon certain diachronic universals or grammaticalization paths. Results: The synchronic inventory of senses of the nominal kaŊ form (i.e. progressive, continu- ous, progressive-iterative, iterative, habitual and durative values) shows that this construction can be mapped using the imperfective path as a template of chaining. this mapping, hypothesized on the ground of synchronic semantic evidence and typological diachronic laws, is next corroborated by the structural properties of the nominal kaŊ locution, especially by its locative and nominal character. Conclusion: all the evidence enables the author to semantically define the nomkaŊ form as a non- advanced imperfective-path gram. part 1: In the second article of the series, the author designs the map of the semantic potential of the nominal kaŊ locution and corroborates it by analyzing formal properties of this construction.